2019
DOI: 10.1097/corr.0000000000000659
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Impact of a Previous Femoral Osteotomy on THA? A Systematic Review

Abstract: Background Femoral osteotomies have been widely used to treat a wide range of developmental and degenerative hip diseases. For this purpose, different types of proximal femur osteotomies were developed: at the neck as well as at the trochanteric, intertrochanteric, or subtrochanteric levels. Few studies have evaluated the impact of a previous femoral osteotomy on a THA; thus, whether and how a previous femoral osteotomy affects the outcome of THA remains controversial. Each author certifies that neither he or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
(137 reference statements)
0
17
0
Order By: Relevance
“…The medical literature reports increased operative time and complication rates when the removal of previously implanted hardware is performed at the same time of THA [38]. This supports routine implant removal in children with a high likelihood of future THA [39]. In most of these patients, the choice of the appropriate surgical approach requires an understanding of the local anatomy to optimize joint visualization [28].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The medical literature reports increased operative time and complication rates when the removal of previously implanted hardware is performed at the same time of THA [38]. This supports routine implant removal in children with a high likelihood of future THA [39]. In most of these patients, the choice of the appropriate surgical approach requires an understanding of the local anatomy to optimize joint visualization [28].…”
Section: Discussionmentioning
confidence: 93%
“…The second factor is the severity of osteoarthritis. An osteotomy performed on an already osteoarthritic bone would at best result in only a short-term improvement of symptoms and could represent a complicating factor for the future THA surgery [39]. Furthermore, regardless of whether the osteotomy fixation hardware is removed at another surgery, or during the index THA, thus prolonging the surgical times, the risk of subsequent periprosthetic joint infection is theoretically increased [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Fukuri et al reported similar functional results to patients who underwent THA in the presence of a rotational acetabular osteotomy [21]. Even in the case of the Bernese osteotomy, Parvizi et al concluded that subsequent THA for DDH was not compromised [22] . On the other hand, poorer functional outcomes have been reported after combined periacetabular osteotomy (PO) and intertrochanteric valgus osteotomy [4].…”
Section: Discussionmentioning
confidence: 94%
“…The articular capsule is thickened and upwards elongated, while the function of the abductors is impaired. With the possible exception of the abductors, all the muscles around the hip joint are shortened in both low and high dislocations [22,23]. In most cases, brave intraoperative soft tissue release and tenotomies are advocated [24,25,26,27].…”
Section: Surgical Pearls and Challengesmentioning
confidence: 99%